1999
DOI: 10.1039/a806728g
|View full text |Cite
|
Sign up to set email alerts
|

Crystallinity of boehmite and its effect on the phase transition temperature of alumina

Abstract: The effect of the crystallinity of boehmite powders on the temperatures of c-Al 2 O 3 formation and the h-to a-Al 2 O 3 transformation was investigated using boehmite powders of varying crystallite size prepared under various hydrothermal conditions. With increasing crystallite size of the boehmite powders, the specific surface area decreased and the expanded (020) d-spacing approached the reported value. Thermogravimetric ( TG) profiles of more poorly crystalline boehmite indicated the presence of excess wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(98 citation statements)
references
References 18 publications
3
83
1
1
Order By: Relevance
“…Contrary to the results reported in the literature [10,27,28], treatment at 723 K for 45 min does not appear to be sufficient to complete this conversion. It is in fact observed that the wide bands around 3400 and 3200 cm −1 are still present and that the OH stretching bands above 3650 cm −1 , typical of alumina, are not yet clearly defined (Fig.…”
Section: Conversion Of Mo-boehmite To Mo-al 2 Ocontrasting
confidence: 56%
“…Contrary to the results reported in the literature [10,27,28], treatment at 723 K for 45 min does not appear to be sufficient to complete this conversion. It is in fact observed that the wide bands around 3400 and 3200 cm −1 are still present and that the OH stretching bands above 3650 cm −1 , typical of alumina, are not yet clearly defined (Fig.…”
Section: Conversion Of Mo-boehmite To Mo-al 2 Ocontrasting
confidence: 56%
“…The α-Al 2 O 3 phase of polymorphic aluminum oxides is known to form at temperatures above 1000 o C. 15 The blue CAO crystallite contents in the samples prepared at 210 o C could be determined using the maximum value of the (311) peak. The sample concentrations obtained from the 31-, 35-and 39-precursors were 66, 80 and 71%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…According to Refs., [1,21,36] it can be assumed that the strong endothermal peak and the large weight loss of approximately 13.7% appearing near 540 C correspond to the transformation of boehmite to g-Al 2 O 3 . Tettenhorst [37] and Tsukada et al [38] have shown that the transition temperature decreases with decreasing size of the boehmite crystallites. Thus, the weak endothermal peak and the weight loss of nearly 2% starting behind 350 C might be attributed to the transformation of small boehmite crystallites.…”
Section: Formation Of G-al 2 Omentioning
confidence: 99%
“…Alternatively, the first endothermal peak and the weight loss of nearly 2% can be attributed to the release of water adsorbed on the surface of boehmite crystallites or intercalated in the interlayers of the crystal structure. [1,38] In order to verify this hypothesis, additional information about the location of the water molecules and about the water content in annealed boehmite was obtained from the Raman investigations, which were performed in the wavenumber range 2900-3800 cm À1 on samples calcined for 20 h at the temperatures between 300 and 600 C (Figure 3). The modes appearing between RT and 400 C can be related to different ÀOH stretching vibrations.…”
Section: Formation Of G-al 2 Omentioning
confidence: 99%